Quelques théorèmes sur les séries de Dirichlet - Tourpanova, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. М. Турпанова. Некоторые теоремы о рядах Дирихле V. Turpanova. Kai kurios teoremos Dirichle eilučių klausimu